Biological interactions at different spatial scales in the Monte desert of Argentina - Bertiller, Monica Beatriz (2009)
In this review, we compiled published results on biological interactions at different spatial scales in the Monte desert of Argentina and identified gaps in current knowledge. We presented evidence of competitive and facilitative plant-plant conspecific and heterospecific interactions, and plant-soil-microbes interactions in relation to the abiotic environment at the fine patch-scale. We also showed evidence of animal-animal interactions and plant-animal interactions at the community scale through study cases involving both native and introduced herbivores. Moreover, we identified bottom-up and top-down forces governing the interactions between granivores (birds, ants, and small mammals) and seed availability/production at the community scale. At the landscape scale, we discussed feedbacks between domestic grazers and the spatial patterns of resources and their interrelationships with processes occurring at other scales. We concluded that research has steadily increased during the last 6 years but knowledge on biological interactions in the Monte desert is still scarce, particularly at a landscape scale.